UPAYA PENINGKATAN PELUANG BISNIS MELALUI RECRUITMENT TENANT PRODUK INOVASI - Esa Indah Ayudia; Tia Wida Ekaputri Hz; La Ode Reskiaddin; Ave Olivia Rahman; Miftahurrahmah; Maulidia Imastary Tan (Universitas Jambi, 2022)
ABSTRACT Jambi University has the vision to become a World Class Entrepreneurship University so that the system in higher education leads to the development of young entrepreneurs to support Indonesia's economic development, especially in the Jambi region. One of the steps to support the vision of the University is to do community service that can improve the economy of both small and medium enterprises. The service carried out this time is related to the promotion and development of young entrepreneurs who are members of the Inkubator Bisnis dan Teknologi (IBT) FKIK Unja, especially in the Recruitment Tenant segment. The participants who are part of this community service are tenants of IBT FKIK who were recruited through registration forms and interviews. The selected tenants are young entrepreneurs educated by resource persons with lecture and discussion methods to promote innovative products to the broader community and understand that increasing the quantity and quality of products can provide more excellent opportunities to connect with investors or other partners. This service activity was well received by the tenants, who are young entrepreneurs. Based on participants' responses, this activity provides positive benefits in preparing for the long-term business development they are starting. Keywords: business, entrepreneur, networking, recruitment tenant ABSTRAK Universitas Jambi memiliki visi untuk menjadi a World Class Entrepreneurship University, sehingga sistem dalam perguruan tinggi mengarah pada pengembangan wirausahawan muda untuk mendukung perkembangan ekonomi Indonesia khususnya di wilayah Jambi. Salah satu langkah untuk mendukung visi Universitas adalah dengan melakukan pengabdian kepada masyarakat yang dapat meningkatkan perekonomian baik yang bersifat usaha kecil maupun menengah. Adapun pengabdian yang dilakukan kali ini, yakni berkaitan dengan promosi dan pembinaan pengembangan usaha entrepreneur muda yang tergabung dalam Inkubator Bisnis dan Teknologi (IBT) FKIK Unja khususnya pada segmen Recruitment Tenant. Adapun peserta yang menjadi bagian dalam pengabdian masyarakat ini adalah tenant-tenant yang tergabung dalam IBT FKIK yang direkrut melalui pendaftaran formulir dan wawancara. Para tenant yang terpilih merupakan para entrepreneur muda diedukasi oleh narasumber dengan metode ceramah dan diskusi agar dapat mempromosikan produk inovasi kepada masyarakat luas serta memberi pemahaman bahwa dengan cara meningkatkan kuantitas dan kualitas produk dapat memberikan peluang lebih besar untuk terhubung dengan investor atau mitra kerja lainnya. Kegiatan pengabdian ini diterima baik oleh para tenant yang merupakan entrepreneur muda. Dilihat dari respon peserta, kegiatan ini memberikan manfaat positif dalam mempersiapkan pengembangan usaha jangka panjang yang mereka rintis. Kata kunci: bisnis, entrepreneur, networking, recruitment tenant